Causation Fallacy 2.0: Revisiting the Myth and Math of Affirmative Action. (January 2016) - Hughes, Sherick; Thompson Dorsey, Dana N.; Carrillo, Juan F.
Justice Goodwin Liu reexamined seminal affirmative action in higher education legal cases beginning with the landmark 1978 case, Regents of the University of California v. Bakke and leading up to the U.S. Supreme Court's 2003 decision in Gratz v. Bollinger . Liu argued that the Bakke and Gratz lawsuits were grounded in an underlying causation fallacy, largely because neither case involved enough applicants of color to change the likelihood of Bakke's and Gratz's admittance. Recent lawsuits from self-identified White and Asian, rejected applicants have emerged against top-ranked universities. This article revisits Liu's assertions by applying his critical approach to those cases. Data indicate too few applicants of color to change the likelihood of recent plaintiffs' admittance. Concluding arguments name Causation Fallacy 2.0 as a useful tool for explaining the cultural politics of race surrounding affirmative action admissions cases.